2022
DOI: 10.1101/2022.03.07.483338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential DNA methylation in Pacific oyster reproductive tissue in response to ocean acidification

Abstract: Background: There is a need to investigate mechanisms of phenotypic plasticity in marine invertebrates as negative effects of climate change are experienced by coastal ecosystems. Environmentally-induced changes to the methylome can regulate gene expression, but methylome responses may be tissue- and species-specific. To assess how ocean acidification affects the Pacific oyster (Crassostrea gigas) epigenome, we exposed oysters to either low pH (7.31 ± 0.02) or ambient pH (7.82 ± 0.02) conditions for seven week… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(231 reference statements)
0
1
0
Order By: Relevance
“…When examining partial pressures of CO 2 , it was found that exposure to elevated levels caused proteins associated with the cytoskeleton, such as actin isoforms, and oxidative stress to be upregulated (Tomanek et al, 2011). Analysis of gonad methylomes in Pacific oysters also showed genes associated with protein ubiquitination to be differentially methylated in response to differing pH levels (Venkataraman et al, 2022). Here, we found that glutathione S-transferase was upregulated in GA and MA at 20°C, and higher activity of this protein has been found in M. edulis extracted from sites with high pollution (Fitzpatrick et al, 1997), which can alter pH levels.…”
Section: Discussionmentioning
confidence: 99%
“…When examining partial pressures of CO 2 , it was found that exposure to elevated levels caused proteins associated with the cytoskeleton, such as actin isoforms, and oxidative stress to be upregulated (Tomanek et al, 2011). Analysis of gonad methylomes in Pacific oysters also showed genes associated with protein ubiquitination to be differentially methylated in response to differing pH levels (Venkataraman et al, 2022). Here, we found that glutathione S-transferase was upregulated in GA and MA at 20°C, and higher activity of this protein has been found in M. edulis extracted from sites with high pollution (Fitzpatrick et al, 1997), which can alter pH levels.…”
Section: Discussionmentioning
confidence: 99%